Modelling goal adjustment in social relationships: two experimental studies with children and adults - Thomsen, Tamara; Kappes, Cathleen; Schwerdt, Laura; Stadler, Johanna; Poller, Charlotte (The British journal of developmental psychology, 2017)
In two experiments, we investigated observational learning in social relationships as one possible pathway to the development of goal adjustment processes. In the first experiment, 56 children (M = 9.29 years) observed their parent as a model; in the second, 50 adults (M = 32.27 years) observed their romantic partner. Subjects were randomly assigned to three groups: goal engagement (GE), goal disengagement (GD), or control group (CO) and were asked to solve (unsolvable) puzzles. Before trying to solve the puzzles by themselves, subjects observed the instructed model, who was told to continue with the same puzzle (GE) or to switch to the next puzzle (GD). Results show that children in the GE group switched significantly less than in the GD or CO group. There was no difference between the GD group and CO group. Adults in the GE group switched significantly less than in the GD or CO group, whereas subjects in the GD group switched significantly more often than the CO group. Statement of contribution What is already known on this subject? Previous research focused mainly on the functions of goal adjustment processes. It rarely considered processes and conditions that contribute to the development of goal engagement and goal disengagement. There are only two cross-sectional studies that directly investigate this topic. Previous research that claims observational learning as a pathway of learning emotion regulation or adjustment processes has (only) relied on correlational methods and, thus, do not allow any causal interpretations. Previous research, albeit claiming a life span focus, mostly investigated goal adjustment processes in one specific age group (mainly adults). There is no study that investigates the same processes in different age groups. What does this study add? In our two studies, we focus on the conditions of goal adjustment processes and sought to demonstrate one potential pathway of learning or changing the application of goal adjustment processes, namely observational learning. We employed an experimental design to study observational learning, instead of using a correlational design. The present studies are the first to apply an experimental design to investigate observational learning of adjustment processes. In our studies, we implemented the same design and studied the same process in different age groups. Thus, they expand knowledge beyond a particular age group and under a life span perspective.